The mystery of the kibble crook - Bridwell, Norman; Lloyd, Gita; Binder, Eric; Bridwell, Norman (New York : Cartwheel books, 2002)
T-Bone eats all of Cleo's new dog food but does not admit it right away.
"Cartwheel books."
"Based on the Scholastic book series 'Clifford the big red dog' by Norman Bridwell."
G1
Keywords: Dogs -- Fiction; Honesty -- Fiction